Adding Value for Customers (Journal of Universal Excellence, 2026)
Research Question (RQ): How or in what way is the excellence of companies in adding value for customers manifested?Purpose: The purpose is to check the results of individual sub-subsets of the selected widget called Adding Value for Clients in two different periods and to compare themMethod: The results of selected periods have been used and compared, and we analyse them and, based on the analysis, propose measures for improvementsResults: The results show fluctuations in the given building block estimates over the selected period, which may be due to various factors.Organization: With the given suggestions, we influence the improvement of the company's excellence. By implementing the proposals, we can further improve the value for customersSociety: Value added for customers is influenced by all stakeholders in the company - management and employees. It is necessary to be aware that they can only be more successful together and with consistent implementation of measures.Originality: Since the results are also from 2020, it means that these are the latest results of the sub-builders, so we can see the influence of the main factor (Covid 19) on the resultsLimitations/Future Research: In order to achieve representative results, it would be necessary to compare the results from previous years and analyse the progress / decline in individual subcontractors.
Keywords: added value; customers; building block; substructures; analysis; measures; stakeholders; company